A Pragmatic Analysis of Deixis in Olivia Rodrigo’s Song “Driver’s License” - Joko Prayudha.S (J-Lalite: Journal of English Studies, 2023)
Deixis is one of the pragmatic aspects that refers to words, phrases, or expressions that have different meanings depending on the contexts of who is speaking and the time and the place where the utterance is expressed. This study aims to analyze the types of deixis found in Olivia Rodrigo's song, "Driver's License". This song is one of the most popular songs today and is widely heard around the world. The research method used is a mixed method through a descriptive approach. The data were obtained by observing the lyrics of the song, which were then analyzed by content to determine the types of deixis in this song. Then, data analysis by using (1) generating the natural unit, (2) classifying, categorizing, and ordering the unit, (3) structuring the content, and (4) interpreting the data. The results of the study show that there are 119 deictic expressions in this song and can be categorized into three types of deixis, namely: person deixis, which refers to the character or noun in an utterance; spatial deixis, which refers to the place or location spoken; and temporal deixis, which refers to the time when the speaker is speaking. By knowing the types of deixis, students can distinguish deixis information through categories that are appropriate based on the types so that they can distinguish the use of deixis based on the situation of the object used.